Effects of Hypertension, Diabetes Mellitus, and Gender on Post Stroke Cognitive Impairment: Meta-Analysis - Sukandriani Utami; Emirza Nur Wicaksono; Amalia Choirunnisa; Nindita Arum Veibiani; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Post-stroke cognitive impairment is a serious problem that is often faced by indivi-duals who have experienced a stroke. This study aims to determine and estimate the effects of hypertension, diabetes mellitus, and gender on post-stroke cognitive impairment through meta-analysis of primary research conducted by previous researchers.Subjects and Method: This was a meta-analysis study using the PICO model which includes; P: post-stroke patients. I: hypertension, diabetes mellitus, and women. C: normotensive, without diabetes mellitus, and men. O: post-stroke cognitive impairment. A systematic search for primary studies was carried out in the PubMed database which was published from 2014 to 2023. The keywords used to search for primary studies were